The Science of Astrobiology A Personal View on Learning to Read the Book of Life - Chela-Flores, Julian (Cellular Origin, Life in Extreme Habitats and Astrobiology, 2011)
Since the publication of The New Science of Astrobiology in the year 2001-the first edition of the present book-two significant events have taken place raising the subject from the beginning of the century to its present maturity. Firstly, in 2001 the Galileo Mission still had two years to complete its task, which turned out to be an outstanding survey of the Jovian system, especially of its intriguing satellite Europa. Secondly, the Cassini Huygens Mission was on its way to Saturn. Its present success has surpassed all the expectations of ESA and NASA. Cassini had been launched four years earlier and Huygens was to land on Titan three years after the publication of the first edition. Besides, astrobiologists had no idea that another satellite of Saturn, Enceladus, was going to force a tantalizing lure on the scientific community with its startling jets of water exuding an air of mystery, hinting at a submerged inhabitable ocean of salty water. Before the date of publication of The New Science of Astrobiology there was not an awareness of the Earth-like features of Titan. Besides, we still had to learn that Titan was the fifth body of the Solar System that possibly contained a water ocean, thus joining our planet and the three Galilean satellites other than Io.           As a multidisciplinary subject, astrobiology sometimes regretfully neglects to some extent the life sciences. There are many other aspects of our culture to keep in mind: chemical evolution, the earth sciences, the physical sciences, cutting-edge technology and the humanities that lie at its frontiers. The emphasis on our previous book made a modest attempt to set the scientific subject squarely amongst other sectors of culture. These boundaries are philosophy and theology, branches of the humanities asking similar questions to the basic issues that are astrobiology's main domain (the origin, evolution, distribution and destiny of life in the universe). The present volume brings these issues up to date.